Integration of interactome and transcriptome data to reveal glucose repression pathway in Saccharomyces Cerevisiae - Hasdemir, Dicle. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Due to glucose’s role as a primary signaling molecule, a change in glucose level immediately stimulates certain elements of the glucose sensing and signaling pathway. This stimulation of the pathway activates the associated regulatory network. In yeast S. cerevisiae, some of the proteins involved in the glucose repression pathway are clearly identified. A key element of the glucose repression pathway; Snf1 kinase is composed of a catalytic subunit Snf1p, a regulatory subunit Snf4p and a scaffolding -subunit (Sip1p, Sip2p or Gal83p). Due to its key role, it is important to predict how the signaling mechanism is affected in the absence of this complex. In this study the genome wide expression data from SNF1D, SNF4D and SNF1DSNF4D mutants were mapped onto the pre-processed protein-protein interaction network of yeast. All the linear paths starting from the glucose importer protein Hxk2p and ending at the transcriptional repressor of gluconeogenic genes Mig1p were identified via NetSearch algorithm. The linear paths were then scored based on the expression levels of the genes encoding the proteins involved. Thus, the key signaling elements of the significantly responsive linear paths were determined. The identified proteins were predicted to be the most likely elements to play a role in the glucose repression mechanism of yeast in the absence of the components of the Snf1 complex. In addition to that, the transcriptome data from these mutants were integrated with the regulatory network of yeast. As the final objective, a complete view of the glucose repression mechanism in the absence of the two constituent proteins of the Snf1 complex was predicted and putative elements with similar roles to this important complex were proposed.
Keywords: Saccharomyces cerevisiae.; Glucose -- Metabolism.